Asatidz's Efforts to Improve the Reading and Writing Ability of the Al-Qur'an of TPA Students - Jumahir; Karmila P Lamadang; Masrion Tahawali; Nurain Labalo (MultiTech Publisher, 2024)
The Al-Qur'an Education Park (TPA) is a non-formal education unit that teaches reading and writing Al-Qur'an letters to children from an early age and instills the morals contained in the Al-Qur’an. The Al-Qur'an Education Park (TPA) aims to make students able to read the Al-Qur'an properly and correctly and use it as a guide to life. The aim of this research is to determine Asatidz's efforts to improve the Al-Qur'an reading and writing skills of students at TPA Al-Istiqomah central market. The subject of this research involves the head of the TPA and the TPA teacher. The methodology for writing this research uses qualitative, data collection uses observation, interview and documentation techniques. The results of the research show that Asatidz's efforts to improve the ability to read and write the Al-Qur'an in students have been maximized by teaching the science of tajwid, providing motivation about the virtues of reading the Al-Qur'an and encouraging them later in the learning process using various methods, namely introducing Hadiyah letters, providing examples of reading, giving assignments and asking questions.